2013
DOI: 10.1159/000356338
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Probiotics in the First 6 Months of Life Did Not Protect against Eczema and Allergy in At-Risk Asian Infants: A 5-Year Follow-Up

Abstract: Background: Healthy gut microflora is essential for oral tolerance and immunity. A promising approach to preventing allergic diseases in genetically at-risk infants is to introduce administration of probiotics early in life when their immune system is still relatively immature. Objective: In this follow-up study, we aim to determine if early-life supplementation with strains of probiotics has any long-term effect on allergic outcomes. Methods: We analyzed the charts and electronic databases of the PROMPT (Prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…If prenatal microbial exposure enhances the preventive effect, as also suggested by epidemiological 71,72 and experimental studies 73 , starting supplementation in the second trimester of pregnancy, when circulating fetal T cells have developed, may be more effective 8 . This may include effects on asthma development, which so far probiotic interventions have failed to prevent [74][75][76][77][78][79][80] . Using non-conventional probiotics such as butyrate and proprionate producers, immunomodulatory strains of West 15 bacteroides 8,30 or clostridia 81 might also induce stronger effects.…”
Section: Probioticsmentioning
confidence: 99%
“…If prenatal microbial exposure enhances the preventive effect, as also suggested by epidemiological 71,72 and experimental studies 73 , starting supplementation in the second trimester of pregnancy, when circulating fetal T cells have developed, may be more effective 8 . This may include effects on asthma development, which so far probiotic interventions have failed to prevent [74][75][76][77][78][79][80] . Using non-conventional probiotics such as butyrate and proprionate producers, immunomodulatory strains of West 15 bacteroides 8,30 or clostridia 81 might also induce stronger effects.…”
Section: Probioticsmentioning
confidence: 99%
“…(43,44) A study from Singapore has shown that consuming probiotics in the first six months of life does not impact allergic outcomes. (45) The timing of introduction of complementary solids in infancy is a persistent source of contention in allergy prevention. It is possible that despite rapid urbanisation in Singapore, maintenance of traditional dietary practices such as early introduction of egg and fish in rice porridge, and peanut in soups may have contributed to the low rates of food allergy.…”
Section: Pr E V Entio N O F Foo D a Llergymentioning
confidence: 99%
“…However, based on a once-yearly follow-up cohort study on children up to the age of 5 years, Loo et al [14 ]found that the early use of probiotics had no significant effect on eczema, asthma, allergic rhinitis, food allergy or sensitization to dust-mite allergens.…”
Section: Introductionmentioning
confidence: 99%